Mazbut Vakıflara Ait Taşınmazları Konu Edinen Kira Sözleşmelerinin_x000D_ Sona Ermesine İlişkin Bazı Tespitler ve Bu Konudaki Güncel_x000D_ Gelişmeler - (:unkn) unknown (My University, 2020)
Mazbut vakıflara ait taşınmazların kiraya verilmesinde Devlet İhale Kanunu uygulanmaktadır. Bu Kanunagöre hazırlanan tip kira sözleşmesinde kira süresinin geçmesi bir sona erme sebebi olarak gösterilmiştir.Mazbut vakıfların konut ve çatılı işyeri niteliğindeki taşınmazlarının da kira sözleşmesinin konusu olabileceğidikkate alındığında bu sebebin söz konusu taşınmazları konu edinen kira sözleşmelerini sona erdirdiğikabul edilmemelidir. Vakıflar Kanununa eklenen yeni düzenlemede, üç aylık kira bedelinin ödenmemesisözleşmeyi sona erdiren ve taşınmazın tahliyesini gerektiren bir sebep olarak belirtilmiştir. Mazbut vakıflaraait taşınmazların onarım veya inşa karşılığı kiralanmasını konu edinen kira sözleşmelerinin bu sebeplesona ermesi halinde tahsil edilemeyen kira alacağı ve tahliye masrafları da alınan teminattan mahsup edilir.

The State Procurement Law is applied in the renting of immovable properties owned by pious foundations._x000D_ In the type rent contract prepared according to this Law, the lapse of the rental period is shown as a_x000D_ reason for expiration of the contract. Considering that the immovable properties of the foundations as_x000D_ dwelling house and roofed workplaces may also be the subject of the rent contract, this reason should not_x000D_ be accepted to expirate the rent contracts that are the subject of these immovable properties. In the new_x000D_ arrangement added to the Law of Foundations the absence of the three-month rental fee was stated as_x000D_ a reason that expirate the contract and required the evacuation of the immovable property. In the event_x000D_ that the rent contracts that deal with the rent of the immovable properties of pious foundations for repair_x000D_ or construction are expirated due to this reason, the unpaid rent receivable and evacuation costs are also_x000D_ deducted from the pecuniary warrant.
Some Determinations on the Expiration of Rental Contracts on Immovable Properties of Pious Foundations and Current Developments in This Issue